ASSESSMENT OF THE PUBLIC’S PERCEPTION OF THE GROWING ROLE OF WOMEN AS BREADWINNERS AND ITS IMPLICATIONS FOR GENDER EMPOWERMENT IN IMO STATE - Nnah, Florence C. (African Journal of Social and Behavioural Sciences, 2021)
This study assessed the public‟s perception of the growing role of women as breadwinners in the family, identifies the perceived challenges constraining women empowerment, determined the prospects for women empowerment as a means for sustainable development in Owerri Imo State. Two theories- the theory of political economics and the sphere theory were used to provide explanation for the phenomenon of women breadwinners. Data for the study was generated using a specially designed instrument- structured questionnaire. The target population of the study was members of the public from the Owerri metropolis but limited to a sample size of 384. Data obtained were analyzed using descriptive statistical tools including sample percentage, frequency, and mean. The study shows that women are fast, assuming responsibility of heading households and becoming breadwinners. However, in spite of this, women are still constrained based on gender under consideration which prevents them from participating actively like their male counterparts in the workplaces, business and communities in leadership roles. The paper concludes that women empowerment is a key factor for sustainable development but however recommends that women be seen as economic actors in the family and by extension the community and be given opportunities to play roles that would enhance and sustain growth and development.